THE IMPLEMENTATION OF DISCOVERY LEARNING BY USING SCREENCAST-O-MATIC APPLICATION ON STUDENTS' CRITICAL THINKING AND COMMUNICATION SKILLS IN LEARNING CLIMATE CHANGE - Hanifah Diana Putri, - (2020)
Digital competence is a new ability for educators and students in 21st century learning. Digital competence involves the confident critical use of information and communication ability. The purpose of this research was to investigated students' critical thinking and communication skills by implementing discovery learning by using screencast-o-matic application in learning climate change. This research is pre-experimental method with one group pre-test post-test design. Pre-test and post-test was used as data collection tools. The participant of this study were seventh grade students which consists of 26 students from one of junior high school in Bandung. The data of students' critical thinking ability concluded there is improvement on students' critical thinking skills after treatment. N-gain score of critical thinking skills obtained 0.46, which is interpreted as medium improvement. The highest improvement is in Practicing Thinker category and the lowest improvement is in Advance Thinker category. Whereas, the data of students' communication skills resulted there is enhancement between pre-test and post-test. N-gain score of communication skills obtained 0.21, which is interpreted as low improvement. The most improvement is in Proficient category and the lowest improvement is in Basic category. The correlation between students' critical thinking and communication skills obtained strong correlation category with the coefficient correlation of 0.716. Therefore, discovery learning by using screencast-o-matic can be used to gain students' critical thinking and communication skills.